Ho Chi Minh’s Ideology on Intellectuals: Construction and Application in Contemporary Vietnam - Tien Sy, Nguyen (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
This discussion explores Ho Chi Minh’s ideology regarding intellectuals and its relevance to modern Vietnam. It examines his perspectives on the roles and responsibilities of intellectuals in national development, emphasizing the integration of knowledge with practical application for the benefit of society. The analysis highlights how his principles can guide current efforts in cultivating a robust intellectual workforce that aligns with Vietnam's goals for industrialization and modernization, fostering collaboration between intellectuals, workers, and farmers to drive the nation's progress. Key strategies for implementing Ho Chi Minh’s thoughts in today’s context will also be addressed, focusing on enhancing education, promoting critical thinking, and ensuring that intellectual contributions effectively address societal needs.